2019
DOI: 10.1038/gim.2017.181
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive pharmacogenetic testing: exploring the knowledge and perspectives of US payers

Abstract: PURPOSE Preemptive pharmacogenetic testing aims to optimize medication use by having genetic information at the point of prescribing. Payers’ decisions influence implementation of this technology. We investigated U.S. payers’ knowledge, awareness, and perspectives on preemptive pharmacogenetic testing. METHODS A qualitative study was conducted using semi-structured interviews. Participants were screened for eligibility through an online survey. A blended inductive and deductive approach was used to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…However, further studies are needed to fill in significant gaps in evidence that can help us understand the existing barriers, including lack of guidance on how to use PGx information and skepticism from payers regarding the effect of PGx-guided therapy on outcomes, aversion to adverse drug events, and evidence of long-term benefits. 41,42 Therefore, the value of pre-emptive panel testing should be investigated and the barriers to implementing these tests should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are needed to fill in significant gaps in evidence that can help us understand the existing barriers, including lack of guidance on how to use PGx information and skepticism from payers regarding the effect of PGx-guided therapy on outcomes, aversion to adverse drug events, and evidence of long-term benefits. 41,42 Therefore, the value of pre-emptive panel testing should be investigated and the barriers to implementing these tests should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…35 While these recent developments are promising, the reimbursement landscape for pharmacogenetic tests, particularly multiple-gene tests, still remains uncertain, as payers grapple with questions about clinical utility and application, economic utility, and impact on coverage policies. [36][37][38][39] Lack of evidence is often cited as a major barrier to pharmacogenetic test use and insurance coverage. Phillips and colleagues suggested some potential solutions for remedying this evidence gap: (1) document what evidence is lacking, (2) standardize testing procedures and interpretation, (3) provide incentives for closing evidence gaps, and (4) develop creative approaches to obtaining evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they pointed out that many low-cost generic drugs are often available that patients could be prescribed before resorting to a new drug that would require panel genotyping before safely using it. 39 But several studies have shown that preemptive pharmacogenomic testing could not only benefi t patients, it may also be costeffective over the long term. In a systematic review, Verbelen et al 40 assessed 44 economic evaluations that covered 10 of the known pharmacogenomic-associated drugs listed by the FDA.…”
Section: ■ Is Pharmacogenomic Testing Cost-effective?mentioning
confidence: 99%